Factors affecting the shrinkage of fly ash geopolymers - Ridtirud,C. (University of Science and Technology Beijing, 2015)
The shrinkage of fly ash geopolymers was studied in the present study. Fly ash was used as the source material for making the geopolymers. The effects of the concentration of NaOH, sodium silicate-to-NaOH ratio, liquid-to-ash ratio, curing temperature, and curing time on shrinkage were investigated. The geopolymers were cured at 25, 40, and 60°C, respectively. The results indicate that the shrinkage of geopolymers is strongly dependent on curing temperature and liquid-to-ash ratio. The increase in shrinkage is associated with the low strength development of geopolymers. It is also found that NaOH concentration and sodium silicate-to-NaOH ratio also affect the shrinkage of geopolymers but to a lesser extent. © 2011 University of Science and Technology Beijing and Springer-Verlag Berlin Heidelberg.